1991
DOI: 10.1128/mmbr.55.3.335-348.1991
|View full text |Cite
|
Sign up to set email alerts
|

Fluorogenic and chromogenic substrates used in bacterial diagnostics.

Abstract: ular emphasis on methods for specific detection of Escherichia coli. DETECTION OF ENZYMATIC ACTIVITIES General Considerations Three groups of fluorogenic and/or chromogenic reactions have been used. (i) The first is hydrolysis of synthetic substrates by bacterial enzymes, causing considerable increase in the fluorescence and/or absorption of the bacterium-substrate mixture (16). Fluorogenic synthetic enzyme substrates containing coumarin derivatives of 4-methylumbelliferone (4-MU) or 7-amino-4-methylcoumarin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
104
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(110 citation statements)
references
References 97 publications
2
104
1
3
Order By: Relevance
“…The use of media containing substrates for the enzyme b-dglucuronidase for the detection of Escherichia coli in water has become widely adopted in many regions of the world (Cowburn et al 1994;Eckner 1998;Edberg et al 1988;Manafi et al 1991) and such methods have been shown to be more specific than methods based upon fermentation of lactose and production of indole from tryptophan at 44°C (Fricker et al 2008). However, it is clear that not all such media perform equally (Fricker and Fricker 1996;Niemela et al 2003;Fricker et al 2008;Olstadt et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The use of media containing substrates for the enzyme b-dglucuronidase for the detection of Escherichia coli in water has become widely adopted in many regions of the world (Cowburn et al 1994;Eckner 1998;Edberg et al 1988;Manafi et al 1991) and such methods have been shown to be more specific than methods based upon fermentation of lactose and production of indole from tryptophan at 44°C (Fricker et al 2008). However, it is clear that not all such media perform equally (Fricker and Fricker 1996;Niemela et al 2003;Fricker et al 2008;Olstadt et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Kramer and Liu 2002). However, the limitations of 4-MU are well-recognized (Manafi et al 1991) and several studies have described the synthesis of novel umbelliferones with lower pK a values (Goodwin and Kavanagh 1950;Sherman and Robins 1968;Koller and Wolfbeis 1985;Wolfbeis et al 1985). Substrates based on such fluorophores have been shown to be particularly advantageous for the assay of enzymes that have a nonalkaline pH optimum (Tsvetkova et al 1996;Gee et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…derivatives of 4-MU are widely used for detection of bacterial enzymes such as b-galactosidase, b-glucuronidase and b-glucosidase (Manafi et al 1991;Dealler 1993). Such assays have been widely applied in the water industry as these enzymes provide convenient markers for the detection of coliforms, Escherichia coli and enterococci respectively (Berg and Fiksdal 1988;Edberg et al 1988;Clarke et al 1991;Brenner et al 1993;George et al 2000;Caruso et al 2002;Kramer and Liu 2002;Pope et al 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Substrates based on 4-methylumbelliferone (4-MU) have been used extensively for the detection of enzymes in diagnostic microbiology (Mana® et al 1991;Dealler 1993;James 1994). This is due to the ease of hydrolysis and intense¯uorescence generated on release of 4-MU from the substrate by speci®c enzymes (Berg and Fiksdal 1988;Shadix and Rice 1991;Brenner et al 1993).…”
Section: Introductionmentioning
confidence: 99%